PENGURUSAN SURAT DI KANTOR PERPUSTAKAAN DAN ARSIP DAERAH KABUPATEN KEBUMEN - , IMADA HAQUE; , Drs. Machmoed Effendhie, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This graduating paper discuss mail handlingactivitiesin Sub Bagian Tata Usaha Kantor PerpustakaandanArsip Daerah KabupatenKebumen. The purpose of this activitiesâs implementation is to find out the procedures of mail handlingin Kantor PerpustakaandanArsip Daerah KabupatenKebumen. The scope which is discussed in this graduating paper are application of archival system especially the procedures of mail handlingand recovery process. In the research methods of collecting data, the writer uses three methods